Improved methods to transform frequency-dependent complex stiffness to time domain. - Nakamura, Naohiro (Earthquake engineering & structural dynamics.)
A method to transform the frequency-dependent complex stiffness to the impulse response in the time domain was proposed in the previous paper. However, there is a problem in that the accuracy and the convergence of the transformed impulse response are not good in some cases. Moreover, the hysteretic damping was not considered in the previous study although it is essential for practical purposes. In this paper, transform method improvements are proposed. First, the accuracy and the convergence are improved by taking the concept of virtual mass into account. Then, a more improved method for transforming the complex stiffness with large hysteretic damping to the time domain is proposed using the least square method. It is well known that the rigorous transform of the hysteretic damping is impossible because it is non-causal. So this method is thought to be an approximate causalization process.